KLATKAT SEBAGAI SARANA UPAKARA/ UPACARA YADNYA - Ida Ayu Putu Sari; I Nengah Artawan (WIDYANATYA, 2021)
Hinduism is known as a religion that has many ceremonies. The existence of ceremonies in Bali cannot be separated from the means of ceremony, and one of them is the Klakat. Klakat in Balinese Hindu teachings can also be philosophized as 3 frameworks of Balinese Hinduism where if we can combine these things, harmony in life will be able to feel good for ourselves and also our families and the vibrations will extend to the entire universe. frameworks in Balinese Hinduism include:Tatwa: In short, tatwa is the way we carry out religious teachings by deepening religious knowledge and philosophy.Moral: is the way for us to be religious by controlling our daily thoughts, words and actions so that they are in accordance with religious principles. Ceremony: is a religious activity in the form of the Yadnya ritual, which is known as the PancaYadnya: Dewa, Rsi, Pitra, Manusa, and Bhuta Yadnya. The ceremonial activities are seen to be carried out more by Hindus in Bali, while the aspects of Tattwa and Susila are not given much attention, whereas according to Weda Sruti, the way of religion in each "yuga" is different. Yuga is a cycle of times whose time in each era is uncertain. The era of the existence of the universe is divided into four yuga, namely Kerta Yuga, Tritya Yuga, Dwipara Yuga, and Kali Yuga. Each period (yuga) is associated with the main elements. The balance of population (humans) with nature (kamadhuk). The influence of the times on human nature. Available natural sources.The Kerta period is said to be the most stable era, namely the small population, good / positive human characteristics, and the availability of abundant natural resources. This stability was further reduced so that in the age of Kali things were much different, especially regarding the diminishing natural resources and human behavior that was further away from dharma. Therefore Hyang Widhi through the Supreme Rsi reminded mankind that the implementation of religious teachings is not the same in every era.